A rare case of Good’s syndrome presented with recurrent COVID pneumonia - Udvass Kumar Kotokey (The Journal of Association of Chest Physicians)
A 45-year-old male patient with a history of thymectomy presented to the emergency with a history of cough, breathlessness, and fever for the past 3 days. He had undergone a thymectomy in the year 2017 for a thymoma. He had no symptoms consistent with myasthenia gravis. He had a history of COVID pneumonia in November 2021 and another episode in July 2022, following which he made a full recovery. The patient also gave a history of recurrent infections of oral candidiasis and herpes labialis, which responded to antifungal and antiviral medications. Considering his history of thymectomy and recurrent infections, his immunoglobulin levels were measured and came out to be low. A diagnosis of Good’s syndrome was made with a very rare presentation with recurrent COVID pneumonia.